Editibility Pemograman CNC-Milling dengan Memperhatikan Pemotongan Ekonomik Sebagai Pengurangan Waktu Proses pada CNC Milling Center Machine - Lobes Herdiman; Susy Susmartini (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2002)
In numerical control, there are five reference angle points in machining workpart surface that be done at the time of determining zero setting of cartesian scale. This process can be classified as surface milling work and cylinder milling work. In generally, workpart machining processes begin using flat end-cutter tools that is fixed with wide of surface machining like make simple of clamp direction with drive surface on reference points and check surface on processing plan of workpart geometric. This paper use two approaches based on geometric differential and analytical theory, namely (a) left hand offset or G54 and (b) right hand offset or G55 from reference angle points of workpart on drive surface. this application describes how to make tools exchange algortihm on CNC milling programming based on final point of tools at workpart machining processes